Prevalence of potassium, phosphate and acid-base abnormalities among CKD patients in central northeast of Thailand - Tangvoraphonkchai, Kamonwan (Chulalongkorn Medical Journal, 2023)
Background : Hyperkalemia, hyperphosphatemiaand metabolic acidosis are common complications among chronic kidney disease (CKD) patients. However, there were several reports of hypokalemia in population resides in the northeast of Thailand. The prevalence of electrolyte imbalance in CKD patients in this region was still unknown. Objective : To study the prevalence of potassium, phosphate and acid-base imbalance in CKD patients in the central northeast of Thailand. Design Cross-sectional descriptive study Setting Roi-et, Mahasarakham, Khonkaen and Kalasin Provincial public health offices. Material and Method : We used specific My SQL query command for retrieving laboratory data between Jan 1st - Dec 31st, 2014 from the databases of four provincial public health offices regarding ICD 9 and 10 of pre-dialysis CKD codes. Result : In total, databases of 31,180 CKD patients were retrieved. The mean estimated glomerular filtration rate (eGFR), serum potassium, phosphate and bicarbonate were 34.7 ± 24.6 ml/min/ 1.73 m2, 4.2 ± 0.7 mEq/L, 4.1 ± 1.6 mg/dL and 24.2 ± 4.3 mEq/L, respectively. CKD 5 had the highest prevalence of hyperkalemia, hyperphosphatemia and metabolic acidosis (39.9%, 41.5% and 40.8%, respectively). The overall prevalences of hyperkalemia and hyperphosphatemia were higher than hypokalemia and hypophosphatemia (30.1% and 30% vs.10.6% and 7%); however, the prevalence of metabolic alkalosis was higher than metabolic acidosis (30.9% vs. 26.1%). The eGFR correlated positively with serum bicarbonate (r = 0.30, p <0.01) and negatively with serum potassium and phosphate (r = -0.19 and - 0.29, p <0.01). Conclusion : Hyperkalemia and hyperphosphatemia were major metabolic complications among CKD patients in the central northeast of Thailand. Contrary to our knowledge, the prevalence of metabolic alkalosis was higher than metabolic acidosis in these patients.